Measuring the mass accretion rates of Herbig Ae/Be stars with X-shooter - Pogodin, M. A. (2012)
We present the results of our observations of eight magnetic Herbig Ae/Be stars obtained with the X-shooter spectrograph mounted on UT2 at the VLT. X-shooter provides a simultaneous, medium-resolution and high-sensitivity spectrum over the entire wavelength range from 300 to 2500 nm. We estimate the mass accretion rates (Ṁacc) of the targets from 13 different spectral diagnostics using empiric calibrations derived previously for T Tauri-type stars and brown dwarfs. We have estimated the mass accretion rates of our targets, which range from 2 × 10–9 to 2 × 10–7 M⊙ yr–1. Furthermore, we have found accretion rate variability with amplitudes of 0.10–0.40 dex taking place on time scales from one day to tens of days. Additional future night-to-night observations need to be carried out to investigate the character of Ṁacc variability in details. Our study shows that the majority of the calibration relations can be applied to Herbig Ae/Be stars, but several of them need to be re-calibrated on the basis of new spectral data for a larger number of Herbig Ae/Be stars (© 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)